Cross‐species comparison of relative potencies and relative sensitivities of fishes to dibenzo‐p‐dioxins, dibenzofurans, and polychlorinated biphenyls in vitro. (January 2016) - Eisner, Bryanna K.; Doering, Jon A.; Beitel, Shawn C.; Wiseman, Steve; Raine, Jason C.; Hecker, Markus
Abstract: Dioxin‐like compounds of varying toxicities are found in complex mixtures. The toxic equivalency factor (TEF) approach was developed based on the potency of a dioxin‐like compound relative to the potency of 2, 3, 7, 8‐tetrachloro‐dibenzo‐ p‐ dioxin (TCDD) to streamline risk assessment. One limitation of the TEF approach is uncertainty regarding differences in the relative potency of dioxin‐like compounds among different species. Relative potencies among fishes are limited, relative to relative potencies among birds and mammals, and TEFs for fishes are based entirely on the model species, rainbow trout ( Oncorhynchus mykiss ). An in vitro liver explant assay was used to characterize species‐specific responses with regard to up‐regulation of CYP1A transcript after exposure to 6 dioxin‐like compounds in rainbow trout, white sturgeon ( Acipenser transmontanus ), lake sturgeon ( Acipenser fulvescens ), and northern pike ( Esox lucius ). Differences in sensitivities were observed among species after exposure to dioxin‐like compounds. The relative potencies developed from liver explants of rainbow trout were comparable to relative potencies developed from embryo toxicity assays. Differences in relative potencies between species with the least and greatest relative potencies were up to 40‐fold. To compare relative potencies among species, concentrations of dioxin‐like compounds in fish eggs in the Fraser River and in Lake Ontario were used to calculate toxic equivalency quotients (TEQs) determined from TEFs or TCDD equivalents determined from relative potencies. The TEQs underestimated TCDD equivalents for white sturgeon, lake sturgeon, and northern pike, indicating uncertainty in application of TEFs to diverse fishes. Environ Toxicol Chem 2016;35:173–181. © 2015 SETAC